EFFECT OF SEEDING RATES AND MOWING STAGES ON GROWTH, YIELD AND QUALITY OF FORAGE AND SEED OF COMMON VETCH (Vicia sativa L.) - Salim Younis (Mesopotamia Journal of Agriculture)
This study conducted in the winter season (2012-2014) at two locations (Bashiqa / Tobzawh village) (25km) east of Mosul and Hemidat - Thaljah village (20 km) west of Mosul. Experiments carried out at each locations to study the effect of three seeding rates (60. 90 and 150kg/ha.) and three growth stages (beginning of flowering, early pod formation and lower pod filing) on growth characters of: forage, seeds yield and quality of common vetch. The experiments carried out according randomized complete block design (R.C.B.D.) with three replacations. The growth stages significantly affect all growth characters dry forage yield and percentage of quality characters of dry forage at both location. The dry forage yield was achieved at lower pod filing growth phase at Thaljah location (3.1ton/ha); And at Tobzawh location (3.6 ton/ha), seeding rates significantly effected dry forage yield at both locations the highest dry forage yield was a achieved with seeding rates 150kg/ha at Thaljah location (2.3 ton/ha) and Tobzawh location(2.6ton/ha) grain yield component and of quality characters of dry forage significantly affect by seeding rates at both location except protein percentage at Thaljah location. The Percentage of all quality characters of seeds and straw were  is significantly affected by seeding rates at both except protein percentage  in seeds and straw at Thaljah location. and percentage of soluble carbohydrate  in seeds, ether extract in straw at Tobzawh location and percentage ether extract in seeds at in seeds at both locations the interaction between   seeding rates and growth stages significantly effect on all  growth characters, dry forage yield and quatily characters of dry forage  yield except ahs percentage at Tobzawh location. The highest dry forage yield was achieved at seeding rates 150 kg/ ha and lower pod filing growth satages at Thaljah location (3.9ton/ha) and at Tobzawh loction (4.3ton/ha.(